Las lógicas racistas frente a la inmigración. La trama de la desigualdad - García Martínez, Alfonso (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The processes of spatial mobility of people and groups with different cultures and traditions (with the resulting positive as well as negative contacts with other cultural forms) nowadays take specific characteristics that basically differentiate them to the past habits. In deed, the configuration of diverse human societies into national States has involved that the presence of people coming from other states acquires automatically, in most occasions, a different socio-political statute, that of foreigners. A statute that does not only conveys juridical expressions but that condition the official discourses about immigration, turning them essentially into negative ones as far as the immigrants is concerned and associating them to dangers for the native people. Such discourses contribute, in its mediatic shape essentially, to the consolidation of a specific symbolic universe, possibly pre-existing, that becomes part of the collective imaginary. Such expressions, which, in its formulation, do not stop being contradictory, favour the conservative thesis about the dangers inherent in the formation of multicultural societies and make remarkably difficult the development of an intercultural perspective.